Investigating public places and impacts of heat stress in the city of Aachen, Germany - Maras, Isabell; Buttstädt, Mareike; Hahmann, Julia; Hofmeister, Heather; Schneider, Christoph (DIE ERDE – Journal of the Geographical Society of Berlin, 2014)
Understanding the role of structure and social aspects regarding heat stress of people in urban areas requires an interdisciplinary scientific approach that connects methods from both natural sciences and social sciences. In this study, we combine three approaches to provide an interdisciplinary analysis of the structure and social components of heat stress in the city of Aachen, Germany. First, we assess the overall spatial structure of the urban heat island using spatially distributed measurements from mobile air temperature recordings on public transport units combined with spatially distributed geo-statistical data. The results indicate that the time of day matters: During the afternoon, areas with a relative low building density, like the industrial area northeast of the inner city, are the warmest, while surfaces in high-building-density areas like the inner city heat up faster during the evening. Second, we combine these measurements with place-based survey data collected in 2010 from residents aged 50 to 92 regarding their individual housing conditions, medical history and social integration to examine the match among heat-based stress of older residents, social conditions and elevated temperatures in their residential quarter. We identify disadvantaged areas for specific already-disadvantaged demographic groups in the city, pointing to a cumulation of inequalities, including heat stress among the most vulnerable. Third, we compare data of biometeorological measurements on urban public squares during the afternoon with results of the micrometeorological model ENVI-met to examine the spatial variability of the inner-city heat load. We complement the modelling results with on-site interviews to evaluate people’s heat perception at the same public places. A simulation shows that additional vegetation would increase thermal comfort at these public places, whereby the heat load assessed using the predicted mean vote (PMV) value would decrease by approximately 60 %. Furthermore, we demonstrate the strengths and weaknesses of heat stress simulation. ENVI-met allows for an overall reasonable representation of heat load during stable atmospheric conditions. However, due to the setup and structure of ENVI-met, large-scale atmospheric changes that occur during the day cannot readily be integrated into ENVI-met simulations.